Primary School Pupils and English Pronunciation in Light of the Emergence of English as a Lingua Franca - Josipović Smojver, Višnja (Array, 2015)
The present research shows that our participants, primary school learners, qualify as future speakers of International English, in particular ELF. In the four-year period of observation of their English pronunciation it has emerged that they are still in the process of mastering what in ELF theory is referred to as the 'core' features of ELF pronunciation. The four core features that turned out to be the most relevant to Croatian learners are the preservation of the identity of the vowel /æ/, the application of the aspiration rule in the right contexts, the maintenance of the contrast between tense and lax vowels, and a level of fluency which does not represent a major obstacle to communication.